How Poor Leadership Skills Elicit Unethical Behavior: Evidence from Public Organizations - Abderrahmane Benlahcene; Houcine Meddour (Universitas Muhammadiyah Yogyakarta, 2022)
Global political and financial entities have witnessed many scandals linked to unethical behaviors of leaders. Previous research suggests that the susceptibility of leaders to act in unethical way finds its roots in various individual, organizational, and social factors. However, unethical leadership is scarcely examined in the context of African countries. The purpose of this study is to explore the role of poor leadership skills and qualities in eliciting unethical leadership behavior in Algerian public organizations. Using an exploratory qualitative approach, 15 leaders and managers were included in series of in-depth interviews. The results of the data analysis reveal that poor leadership skills and competencies are one of the critical antecedents of leadership unethical behavior within Algerian public organizations. This study contributes to the ongoing research efforts that seek to identify and minimize the causes of unethical behaviors of leaders across sectors and disciplines. The study provides insights into the construct of unethical leadership and how individual, organizational, and social factors predict unethical behavior of leaders.